A snapshot of murder : [large type] a Kate Shackleton mystery - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2019)
"Yorkshire, 1928. Indomitable sleuth Kate Shackleton is taking a well-deserved break from her detective work and indulging in her other passion: photography. When her local Photographic Society proposes an outing to the opening of the Bronte Museum, Kate jumps at the chance to visit the setting of Wuthering Heights. But the setting proves to be even more sinister than the dreary classic when a member of their party is found murdered. The event is one of the most popular of the decade, and each of the seven photographers were there to capture the perfect shot of a lifetime. But Tobias, the deceased, was known for being loud-mouthed and didn't care to curb his demeanor. Kate deduces that he must have had several enemies. But soon, she begins to suspect that perhaps the murderer is amongst them. And before they shrink to just a group of five, Kate must pick back up her magnifying glass and sleuthing cap to crack the case."--